The Effects of Education through Role-Playing on Self-Concept among Older Adults - Fatemeh Mansouri; Parand Pourghane; Roya Mansour-Ghanaei; Zahra Atrkar Roushan (Kashan University of Medical Sciences, 2021)
Background: Self-concept (SC) is one the psychological characteristics affected by aging. Objectives: This study aimed to assess the effects of education through role-playing on SC among elderly people. Methods: This quasi-experimental study was conducted in 2018 using a two-group pre- and posttest design. Participants were 72 older adults randomly recruited from retirement centers in the East of Guilan province, Iran, and randomly allocated into control group and intervention group. Participants in the intervention group received education through role-playing in six-weekly sessions. Participants' SC was assessed before the intervention onset and 1.5 months after its end using the Rogers Self-concept Questionnaire. The independent sample t-test, the Mann-Whitney U test, and the Chi-square test were used for the data analysis. Results: There was no statistically significant difference between the intervention and the control groups respecting the pretest mean score of SC (10.69 ± 2.21 vs. 9.77 ± 2.59; P = 0.11). However, the posttest mean score of SC in the intervention group was significantly less than the control group (8.44 ± 2.70 vs. 9.69 ± 2.40; P = 0.046). The pre- and posttest mean difference of SC in the intervention group was also significantly greater than the control group (2.25 ± 2.43 vs. 0.10 ± 1.58; P < 0.001). Conclusion: Education through role-playing is effective in significantly improving older adults' SC. Therefore, health-care providers can use this method for SC improvement among older adults.